Sawer: Melampaui Ruang dan Meluaskan Jangkauan Interaksi pada Pertunjukan Dangdut - Raditya, Michael H.B (UI Scholars Hub, 2022)
This article deals with the issues of sawer that have appeared over time, both in live and online performances. This topic is interesting because sawer is intertwined in the interaction and participation of two active subjects, namely the singer and her audience. In live performances, the exchange between singers and their audiences happens in the same space and time. On the other hand, accommodating sawer in online dangdut performances is a challenge. However, in 2020 there was a lot of interaction and participation—and even sawer—in online shows. I believe this is not the first glimpse of this phenomenon because online sawer places dangdut beyond its physical space and expands the range of interaction between the performer and the audience. In the wider context, this phenomenon is proof of cosmopolitanism and globalization in the online world. According to that hypothesis, this article attempts to articulate the many varieties and complexities of the sawer phenomenon. Although there is an issue about globalization and its impact (read: reduction of diversity), through dangdut—and sawer— the issue can be negotiated freely and easily. In this research, literature studies and digital ethnography will be used to investigate the phenomenon. There are two findings in this research, first, the patterns and process of digital sawer; and second, how society responds to the global world using local ways and logic. It can be concluded that through Dangdut, the global platform is used locally and will remain local, especially looking at the quantity and activeness of Indonesian netizens.